Integrating STEM in Physics Learning to Improve 21st Century Skills: A Systematic Literature Review - Wulandari, Novita; Pujianto (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2025)
21st century skills need to be mastered by learners for education to be of high quality and relevant to the demands of the times. These skills include critical thinking, creative thinking, the ability to collaborate, as well as effective communication skills, all of which are important in facing global challenges and the complexity of the modern workplace. The purpose of this study was to evaluate article reviews on the incorporation of STEM (Science, Technology, Engineering, and Mathematics) into physics teaching to support the development of these skills. The method used was a systematic literature review with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) design consisting of four main stages, namely identification, screening, validity, and inclusion. The Scopus database was used as a search source for relevant scientific articles. A total of 1613 papers discussing STEM integration in physics education were found from 2018 to 2024. Of these, 25 papers were selected based on screening criteria and topic suitability. Based on the data synthesis of these articles, it can be concluded that the application of the STEM approach in physics learning significantly supports the development of 21st century skills. In addition to the four key skills, this integration also has the potential to strengthen civic values and character education through contextualized and interdisciplinary learning approaches. Collaboration between the STEM approach and other innovative learning models, such as problem-based learning or project-based learning, is considered effective in creating deep and meaningful learning experiences for students.